Factors associated with dynamic balance in workers who frequently wear high heels - Tapanya, Weerasak; Sangkarit, Noppharath; Puntumetakul, Rungthip (Archives of Allied Health Sciences, 2019)
Background and Objective: Wearing high heels is considered as normal fashion for working women that influent to decrease in balance and is a high risk of fall. Therefore, the purpose of this study was to define the factors associated with dynamic balance in workers who frequently wear high heels. Method: 28 subjects, age between 21-45 years old who have worn high heeled shoes minimally 5 centimeters, 30 hours per week for at least 1 year, completed subjective about personal demographic data, height of high heeled shoes and duration per week of wearing. They performed ankle dorsiflexion in weight bearing lunge position and Star Excursion Balance Test (SEBT). The Pearson product moment correlation coefficient statistic was used to determine correlation between these variables. Results: The results showed that SEBT score was significantly low to moderate negative correlate with personal demographic data including body weight and height and moderate positive correlate with ankle dorsiflexion ROM. There was not relationship between height of high heel shoes and duration of wearing per week. Conclusion: the workers who frequently wear high heels should consider the factors e.g. ankle dorsiflexion ROM or gastrosolous muscles flexibility, body weight, and body height which can affect dynamic balance performance intensively. If they have less gastrosolous muscle flexibility and high body weight and height, they may increase a risk of fall.